PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. GITA RIAU MAKMR PEKANBARU - Novita Sari; Dewita Suryati Ningsih; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to determine the effect of communication and work environment simultaneously on employee morale at PT. Gita Riau Makmur Pekanbaru and determine the effect of communication and work environment partially at PT. Gita Riau Makmur Pekanbaru. This study uses census method technique , 80 samples were selected as respondents. The analysis method used in this research is descriptive quantitative, analysis of partial and simultaneous (multiple linear regression analysis with SPSS version 17:00). From the results of the testing that has been done, simultaneous regression test (F test) From the results of the testing that has been done, simultaneous regression test. Partial regression test (t test) showed that the working environment variables have a dominant influence on employee morale. The magnitude of the effect that (R2) by these two variables together against the dependent variable of 57.9 % while the remaining 42.15 % is influenced by other variables that are not diteliliti in this study. Thus to improve employee morale, the management needs to pay attention to communication and work environment in the company.Keywords: communication, working environment, and employee morale